Reconstruction of the late Miocene biogeographical history of tits and chickadees (Aves: Passeriformes: Paridae): A comparison between discrete area analyses and probabilistic diffusion approach. (24th September 2017) - Johansson, Ulf S.; Nylinder, Stephan; Ohlson, Jan I.; Tietze, Dieter Thomas
Abstract: Aim: To infer the biogeographical history of the avian clade Paridae (tits and chickadees) using methods based on discrete, a priori defined, geographical areas and a method that uses actual species distributions and a relaxed random walk in a Bayesian context. We compared their relative performances and how different area codings influenced the outcome in the discrete analyses. Location: Holarctic, Indomalaya, Afrotropics. Methods: The phylogeny was reconstructed using Bayesian inference and time‐calibrated using published substitution rates and a fossil calibration point. The discrete analyses were performed in BioGeoBEARS. For the probabilistic diffusion analysis, the extant distribution of each species was shaped as polygons in Google Earth and analysed together with the posterior distribution of time‐calibrated trees inbeast . The diffusion process was modelled as a relaxed random walk. Results: The earliest divergences occurred between 10 and 15 Ma and the probabilistic diffusion analysis, and one of the discrete analyses indicated that the parids originated in the mountains of East Asia (Sino‐Himalayas). Due to a different categorization of the geographical areas, a partly overlapping but conceptually different region was indicated in the second discrete analysis. Between 8 and 5 Ma parids started to spread from the Sino‐Himalayas and became established in North America and Africa before 5 Ma. However, the inferred dispersal patterns differed between the analyses. Main conclusion: Overall, the analyses were congruent and together with the divergence time analysis provided a solid biogeographical history for the parids. However, some discrepancies were evident and the diffusion analysis often indicated a more stationary pattern in the Sino‐Himalayas in contrast to the more widespread ancestors indicated by the discrete analyses. The discrete analyses were influenced both by the biogeographical model and delimitation of the a priori areas.